Buddhist Ethics, and Female Transformation in The Vegetarian - Bhattarai, Sita (Pragnya Sarathi, 2026)
This paper examines how Han Kang’s The Vegetarian reflects the intersectional theme of Buddhist ethics and ecofeminist care for self and other as seen through Yoeng-hye’s prolonged engagement with plant-like simulation. So, the paper, through the intersecting lenses of Buddhist ethics, and women’s empowerment, argues that the novel bases its thematic and structural outline in an ecofeminist–Buddhist perspective through the character of Yeong-hye. While doing so, it seeks how the oppressive conceptual frameworks and dualisms such as man/woman and nature/culture are blurred by challenging anthropocentric and patriarchal structures that justify the domination over nature and women. Under the Buddhist-ecofeminist lens as theoretical position, the study employs textual analysis as method for analysis. Yeong-hye’s decision to eat meat is a key for the exploration of nonviolence, interdependence, and compassion—key indicators of Buddhist thought. While drawing on Findly’s (2002) discussion of Buddhist principle of an egalitarian relationship, the paper highlights the rejection of hierarchies between self and other. Furthermore, Khejoi et al. (2020) emphasize on the combined form of Buddhism, ecology, and feminism, which The Vegetarian articulates and empowers human subjectivity. The study also explores, by positioning Yeong-hye’s resistance of sensory pleasure as a form of spiritual empowerment The Vegetarian reconsiders female subjectivity through an ecofeminist–Buddhist ethic that blurs the binarism to share a theme for an egalitarian relationship between ecological selves.